The founders of the Kyiv Physical-Mathematical Society: Nichola Schyller - Kletska, T. S. (History of science and technology, 2017)
This article highlights the life and scientific-pedagogical activity of one of the founders of Kyiv Physical-Mathematical Society Nichola Schiller, who contributed greatly to the development of physics both in Ukraine and abroad.